Integration and Local Finnish Governments: Local Turn or State Responsibility? - Kettunen, Pekka (Border Crossing, 2021)
Local governments have become more important in the integration of immigrants, constituting a local turn in integration policy. However, the empirical evidence is still limited and variation between countries is presumably high. The present paper analyses the role played by Finnish local governments in the integration process, with municipal governments being highly autonomous from a general European perspective. The paper delineates the basic features of local integration policy, i.e. who does what, and thereafter it assesses the integration plans of local governments and how they justify the current policy. A closer look at Finnish integration policy, however, suggests that state administration actually has a strong role and that most resources are being directed to integration courses administered by the labour administration of the state. What remains for the local governments is to foresee that their services are suitable for immigrants, too. There is an asymmetry between local governments, though, as immigrants mostly live in larger cities, and half of them in the capital city area. While local governments are obliged to assess their integration policies, such assessments mostly deal with outputs and the feedback of service users. In sum, only a weak local turn seems to be emerging in Finland.